(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to identify the most important concerns that led to the increase of interest in the topic of corporate governance and specifically highlighting the role of the audit committees of the Administration Board in reducing the risk of the auditor and the rationalization of professional judgments، in particular about accepting the assignment and setting the fees of the audit process by extrapolating global experience in this area ، and a field study is conducted for a sample of private Iraqi banks to evaluate the role of audit committees constituted currently per with bank law no. (94) of 2004 and to be acknowledged with actual performance of these committees and their role in recommending the nomination of external auditor to be employed، setting the fees for him and being provided with necessary facilities to perform his audit missions by coordinating with internal audit and working as communication channel with administration board، and to follow up how the administration responds to observations mentioned in his report to be tackled and avoided. Then suggested disciplines are concluded to estimate the risk of auditors’ engagement regarding accepting assignment and setting fees. These disciplines are addressed to the Council of Accounting and Auditing profession in Republic of Iraq to assist auditors in dealing with engagement risk and rationalize their professional judgments concerned with that judgment. To accomplish the goals of the research، the following items are studied thoroughly in the field study: Studying and assessing current and actual performance of audit committees in private Iraqi banks as a sample of research by studying released financial annual reports of these companies for the period 2009-2012 ، as well as some officials in directorate general of banking and credit control in the CBI. Design a questionnaire to solicit the views of a number of auditors in the offices and audit firms approved، and distributed (50) questionnaire